OPISTHORCHIASIS. UPDATES ON ECOLOGY AND EPIDEMIOLOGY (Eurasian Journal of Ecology, 2025)
The causative agent of opisthorchiasis, the trematode Opisthorchis felineus (Rivolta, 1884) is one of the most common species of human and animal parasites in Russia, Kazakhstan, and Eastern European countries. Together with closely related species of liver flukes O. viverrini (Poirier, 1886) and Clonorchis sinensis (Loos, 1907), the species endemic to Southeast Asia and the Far East, O. felineus makes up a triad of epidemiologically significant trematodes of the Opisthorchiidae family. Adult worms of O. felineus parasitize the hepatobiliary system of mammals, including humans, and provoke the development of severe complications during chronic infection. However, despite its importance, opisthorchiasis is considered a neglected tropical disease (NTDs). NTDs, affecting 1.65 billion people around the world, are so named for a reason: these diseases, the people and regions they affect, are usually have been overlooked, receiving very little global attention for research, prevention, and control efforts.The review briefly summarizes the results of latest research of the biology and epidemiology of trematodes of the Opisthorchiidae family, discusses the results of studies obtained both on model animals and on patients. The significance the research is emphasized by the complex life cycle of the liver flukes, a prolonged time of the human infection with no apparent symptoms; lack of sufficient information on the effect of helminths on organs not related to the places of their immediate localization, wide distribution of trematodes in endemic geographical areas. Open migration policy and gastronomic tourism expands the geography of the problem of these infections beyond local foci, when patients with opisthorchiasis and clonorchiasis can be found far from endemic areas. Overall, opisthorchiasis can be a serious drain on a country's economy.Keywords: trematodes, opisthorchiasis, systemic disease